Prognostic relevance of left ventricular global longitudinal strain in patients with heart failure and reduced ejection fraction. (3rd October 2022) - Chimed, S; Stassen, J; Galloo, X; Meucci, M C; Van Der Bijl, P; Marsan, N A; Delgado, V; Bax, J J
Abstract: Background: Patients with heart failure (HF) and reduced ejection fraction (HFrEF) are complex patients who often have a high prevalence of comorbidities and cardiovascular risk factors. However, risk stratification and treatment decision in these patients mainly depend on simple measurements of left ventricular (LV) ejection fraction (EF). In the present study, we investigated the prognostic significance of LV global longitudinal strain (GLS) along with important clinical and echocardiographic risk factors in patients with HFrEF. Methods: Patients who had a first echocardiographic diagnosis of LV systolic dysfunction, defined as LVEF ≤45%, were identified. LV GLS was measured with speckle-tracking echocardiography and represented by a positive value. To divide the study population into 2 groups, spline curve analysis was used to derive the optimal threshold value of LV GLS (i.e. where the predicted hazard ratio for the endpoint was ≥1) (Figure 1). Patients were followed up for worsening HF, as well as the composite endpoint of worsening HF and all-cause mortality. Results: A total of 2394 patients (mean age 63±12 years, 75% men) were analyzed. During a median follow-up of 60 months (interquartile range [IQR] 31–60 months), 306 patients (13%) experienced worsening HF and the composite endpoint of worsening HF and all-cause mortality occurred in 673 patients (28%). The 5-year event-free survival rates for the primary and secondary endpoint were significantly lower in the patients who had LV GLS ≤10% compared to the patients who had LV GLS >10% (Figure 2A for worsening HF and Figure 2B for the composite endpoint of worsening HF and all-cause mortality). After adjustment for important clinical and echocardiographic risk factors, including HF treatments and baseline LVEF, baseline LV GLS remained independently associated with a higher risk of worsening HF (HR=0.95, 95% CI 0.90–0.99, p=0.029) and the composite of worsening HF and all-cause mortality (HR=0.94, 95% CI 0.90–0.97, p=0.001). Conclusions: Baseline LV GLS is associated with long-term prognosis in patients with HFrEF, independently from various clinical and echocardiographic risk factors. Funding Acknowledgement: Type of funding sources: None.